OFR-17(3)-77 Conceptual Design Of An Automated Longwall Mining System - Volume I - Final Report ? Executive Summary (The National Institute for Occupational Safety and Health (NIOSH), 1976)
This report provides concepts for two automated longwall mining systems; one for operation in a 42 to 57-inch thick section of the Lower Kittanning coal seam, the other in a 57 to 72-inch thick section of the Pittsburgh seam. The Lower Kittanning concept uses a single-drum bidirectional shearer and 500-ton capacity 4-leg chocks and the Pittsburgh concept uses a double-drum shearer with 500-ton shields. Each concept is designed to produce in excess of 2,500 tons of clean coal per shift with a 6-man face crew. The automated longwalls consist of off-the-shelf control system hardware attached to standard longwall equipment. Control hardware includes a control and display console; prime and backup mini-computers; multiplex data transmission, power, and control lines; several remote terminals which serve as interface junctions; and various sensors and actuators located on the longwall equipment. The system can be operated either fully automatically, remotely or manually.